2022
DOI: 10.1136/gutjnl-2020-323715
|View full text |Cite
|
Sign up to set email alerts
|

Dietary macronutrients and the gut microbiome: a precision nutrition approach to improve cardiometabolic health

Abstract: Accumulating evidence indicates that the gut microbiome is an important regulator of body weight, glucose and lipid metabolism, and inflammatory processes, and may thereby play a key role in the aetiology of obesity, insulin resistance and type 2 diabetes. Interindividual responsiveness to specific dietary interventions may be partially determined by differences in baseline gut microbiota composition and functionality between individuals with distinct metabolic phenotypes. However, the relationship between an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 171 publications
(315 reference statements)
0
44
0
Order By: Relevance
“…One hundred percent of participants were correctly classified as respondents based on basal TNF-α ≤ 7.330 pg/mL. However, although the threshold of 7.330 pg/mL for basal value TNF-α is the best predictor of HbA1c response, 28% of those subjects with values under this threshold will still be nonrespondents, probably because of other factors not measured in this study, which might include genetic polymorphisms and epigenetic regulation of genes involved in carbohydrate and lipid metabolism [54] or microbiome differences between subjects [55,56]. On the other hand, considering the predictive character of this test, this screening method would facilitate the identification of 19% of subjects with prediabetes that would not respond due to high basal TNF-α values, under the conditions used for supplementation in this study.…”
Section: Discussionmentioning
confidence: 79%
“…One hundred percent of participants were correctly classified as respondents based on basal TNF-α ≤ 7.330 pg/mL. However, although the threshold of 7.330 pg/mL for basal value TNF-α is the best predictor of HbA1c response, 28% of those subjects with values under this threshold will still be nonrespondents, probably because of other factors not measured in this study, which might include genetic polymorphisms and epigenetic regulation of genes involved in carbohydrate and lipid metabolism [54] or microbiome differences between subjects [55,56]. On the other hand, considering the predictive character of this test, this screening method would facilitate the identification of 19% of subjects with prediabetes that would not respond due to high basal TNF-α values, under the conditions used for supplementation in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, many studies have demonstrated the relationship between gut microbiota and the homeostasis of lipid metabolism in the host ( 3 , 46 ). Here, our studies provided new evidence that the composition of gut microbiota was closely related to the lipid profiles after BCPs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, dyslipidemia, type 2 diabetes mellitus (T2DM), and other metabolic diseases are related to dysbiosis of gut microbiota profiles ( 2 ). Evidence suggest that obesity and associated metabolic disorders resulted in reduced intestinal microbial richness and diversity and increased the abundance of Firmicutes or the ratio of Firmicutes to Bacteroidetes (F/B ratio) in high-fat diet (HFD)-fed rats ( 3 , 4 ). Diet is an important external factor affecting the gut microbiota, which is considered an important option for the management of the severity of obesity and related chronic diseases ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has revealed the critical role of gut microbiota in maintaining host lipid metabolism [ 2 , 3 , 4 ]. For example, patients with NAFLD had lower microbial diversity than healthy controls [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%